2018
DOI: 10.1001/jamanetworkopen.2018.3344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Barriers to Audit-and-Feedback Programs That Used Direct Observation of Hand Hygiene Compliance

Abstract: Key Points Question How have audit-and-feedback programs based on direct observations of hand hygiene compliance been implemented in real-world settings? Findings In this qualitative study of 108 hospital staff members in 10 acute care hospitals, the use of audit and feedback to improve hand hygiene compliance was problematic. Auditing by direct observation was perceived to collect inaccurate data and created tension with frontline staff, and the feedback p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…Relatedly, the perceptions of the value of QI are inconsistent from one physician to the next, ranging from the belief that it is meaningful and important to the belief that it decreases efficiency and distracts from patient care [ 20 ]. Previous work has documented responses to A&F that primarily reflect organizational perceptions of data [ 7 ], with work at the individual level revealing negative perceptions that interfere with engagement in reflexive monitoring (data is not accurate and is therefore discounted) [ 23 ]. In contrast, many physicians in our study reported that data was imperfect but still accepted it as useful for driving meaningful change in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, the perceptions of the value of QI are inconsistent from one physician to the next, ranging from the belief that it is meaningful and important to the belief that it decreases efficiency and distracts from patient care [ 20 ]. Previous work has documented responses to A&F that primarily reflect organizational perceptions of data [ 7 ], with work at the individual level revealing negative perceptions that interfere with engagement in reflexive monitoring (data is not accurate and is therefore discounted) [ 23 ]. In contrast, many physicians in our study reported that data was imperfect but still accepted it as useful for driving meaningful change in practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a systematic review specific to hand hygiene, Gould and colleagues [4] found it difficult to draw conclusions on whether or not audit and feedback interventions could be sustained, largely due to the Hawthorne effect influence on performance behavior. Our own research building off of the same ethnographic study points to multiple barriers to the use of audit and feedback as a strategy for hand hygiene compliance, particularly when using direct observation as the surveillance method [40]. On the other hand, studies have also shown success with designated HCWs providing immediate hand hygiene feedback [1517].…”
Section: Discussionmentioning
confidence: 99%
“…Schweizer et al [41] completed a systematic review and meta-analysis of hand hygiene improvement trials. Combined results from 39 quasi-experimental and six randomized trials indicated that bundles that included audit and feedback were associated with an 82% increase in hand hygiene [40]. Gould and colleagues [4] found that all 26 studies that met the criteria for inclusion reported some improvement in hand hygiene compliance; however, they were unable to draw conclusions about which interventions or combination of interventions led to clinically important improvements in compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The unevenness in the HE seen in our study raises concerns regarding the accuracy of human auditing and whether it is appropriate to extrapolate audit results to longer periods and larger areas, given the apparently unpredictable differences between the electronic and human auditing compliance numbers. This flaw, in addition to the many other drawbacks of human auditing, which include the need for ongoing training,30 significant time investment yielding limited sample sizes4 31 32 and lack of standardisation,33 has contributed to a perception of inaccuracy by front-line staff 34. Notably, this perception has recently been shared by healthcare workers regarding e-monitoring systems as well, highlighting the argument that no measurement system is perfect 35…”
Section: Discussionmentioning
confidence: 99%